2021
DOI: 10.1371/journal.pone.0249373
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic apparatus performance of tomato seedlings grown under various combinations of LED illumination

Abstract: It is already known that the process of photosynthesis depends on the quality and intensity of light. However, the influence of the new light sources recently used in horticulture, known as Light Emitting Diodes (LEDs), on this process is not yet fully understood. Chlorophyll a fluorescence measurement has been widely used as a rapid, reliable, and noninvasive tool to study the efficiency of the photosystem II (PSII) and to evaluate plant responses to various environmental factors, including light intensity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 72 publications
4
23
1
1
Order By: Relevance
“…The results showed that after plants dark-acclimation the best light mode that squandered excess lowering energy were LM2 and CK ( Fig 6A ), whereas the best treatment squandered excess lowering energy was LM2 after light-acclimation ( Fig 6B ). The results obtained differed from those reported previously other researches [ 16 , 50 52 ], where it was reported that the mixture of red and blue light with a high ratio of red to blue led to an increase of Y(II)max (Fv/Fm).…”
Section: Discussioncontrasting
confidence: 99%
“…The results showed that after plants dark-acclimation the best light mode that squandered excess lowering energy were LM2 and CK ( Fig 6A ), whereas the best treatment squandered excess lowering energy was LM2 after light-acclimation ( Fig 6B ). The results obtained differed from those reported previously other researches [ 16 , 50 52 ], where it was reported that the mixture of red and blue light with a high ratio of red to blue led to an increase of Y(II)max (Fv/Fm).…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, cucumber seedlings grown under equal amounts of R and B light have higher yields compared to seedlings grown under R light only 41 . Yousef and co-authors extended the study to factory tomatoes and showed that illumination with 100 μmol m −2 s −1 70% R and 30% B resulted in the optimal growth of the plants 42 . Moreover, the barrier tissue cells in the leaves were particularly well developed and the spongy tissue cells were arranged in an orderly manner 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The LED lamps (UH-BLDT0510) used in this study were manufactured by Kedao Technology Corporation (Huizhou, China). Tomato seeds were planted 30 days before grafting under 100 μmol m −2 s −1 R7:B3 (red ~ 70: blue ~ 30), which was chosen as the best LED source in our previous research 54 , 55 . The seeds were sown in trays (W 28 cm × L 54 cm × H 5 cm, Luoxi Plastic Products Co., Shandong, China) filled with the commercial growing substrate (N 1 :P :1 K 1 ≥ 3%, Organic matter ≥ 45%, pH 5.5–6.5, Jiangping Enterprise Co., Fujian, China).…”
Section: Methodsmentioning
confidence: 99%